MOTIVASI MAHASISWA S1 AKUNTANSI 2009 PADA UNIVERSITAS NEGERI SURABAYA UNTUK MELANJUTKAN PENDIDIKAN (PPAK DAN S2 AKUNTANSI) - PURITAN, NISA (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is to know what is motivation students of S1Accounting 2009 Unesa to continuing education, in PPAk and S2 Accounting.There are four kinds of motivation can be reference. That is the quality motivation,career motivation, economic motivation and social motivation. Beside that, thisresearch also reviewed the selection of students continuing their education toPPAk or S2 Accounting. Remind to much labor recruitment of find processaccountancy graduate and more high rivality of global work on the world. Thisresearch uses a descriptive qualitative method. The type of data is primary dataobtained through interviews. The technique to determining informant using thesnowballing technique at firstly they only 10 respondents and then increase become20 respondents. The result of this research showing students motivation tocontinuing their education are quality motivation, career motivation, economicmotivation, social motivation, motivation of parents demand and motivation to getAk/M.Ak’s degree. The result showing that quality motivation is the most highmotivation than the other motivation to continuing education. Beside that, the moststudents prefer to continue S2 Accounting education that students believe morecompetent than PPAk.Key words: motivation, PPAk, S2 Accounting